Pengaruh Penerapan Metode Pembelajaran Talking Stick Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Agama Islam di Madrasah Ibtidaiyah Palembang - Hidayanti, Nur Afni; Maryamah, Maryamah; Saputra, Agra Dwi; Fadil, Achmad; Tauhid, Imam (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is motivated by the lack of awareness of teachers to get used to using various learning methods. This can be seen from the technique in learning which still involves lectures, question and answers, and group discussions. Therefore there is a need for a solution to increase student motivation in class.The aims of this study were to 1) find out the learning motivation of control class students without the Talking Stick learning model applied, 2) find out the experimental class students' learning motivation using the Talking Stick learning model applied, 3) find out whether the effect of the application of the Talking Stick learning model on student learning motivation . The research method used is a quantitative method. The collection of data used is observation, documentation, and questionnaires. The results showed that there was an influence of the Talking Stick learning method on students' motivation in Islamic religious subjects in class V Mi Mambaul Hidayah II Palembang. This can be seen from the percentage value of hypothesis testing using the t-test formula obtained tcount = 4.396. from the t distribution table at a significance level of 5% obtained ttable = 2.120. from these results it can be concluded that, tcount > ttable, namely 4.396 > 2.120, then Ho is rejected and Ha is accepted, meaning that the scores of students' learning motivation given treatment using the Talking Stick Learning method are higher than the scores of students' learning motivation without being given treatment